2020
DOI: 10.1186/s12936-020-03368-5
|View full text |Cite
|
Sign up to set email alerts
|

Particle-based, Pfs230 and Pfs25 immunization is effective, but not improved by duplexing at fixed total antigen dose

Abstract: Background: The Plasmodium falciparum sexual-stage surface proteins Pfs25 and Pfs230 are antigen candidates for a malaria transmission-blocking vaccine (TBV), and have been widely investigated as such. It is not clear whether simultaneously presenting these two antigens in a particulate vaccine would enhance the transmission reducing activity (TRA) of induced antibodies. To assess this, immunization was carried out with liposomes containing synthetic lipid adjuvant monophosphoryl lipid A (MPLA), and cobalt-por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The combination of RTS,S/AS01 with a viral vector PEV (ChAd63/MVA ME-TRAP) failed to improve the vaccine e cacy as compared to the two vaccines administered individually [33]. For a bivalent TBV design, the combination of Pfs25 and Pfs230C1 did not enhance the antibody response when compared to single antigen immunization [23]. In this study, we tested speci c antibody responses against the rPbg37 and rPSOP25 fragments and demonstrated that these two protein fragments did not interfere with each other in inducing functional antibodies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The combination of RTS,S/AS01 with a viral vector PEV (ChAd63/MVA ME-TRAP) failed to improve the vaccine e cacy as compared to the two vaccines administered individually [33]. For a bivalent TBV design, the combination of Pfs25 and Pfs230C1 did not enhance the antibody response when compared to single antigen immunization [23]. In this study, we tested speci c antibody responses against the rPbg37 and rPSOP25 fragments and demonstrated that these two protein fragments did not interfere with each other in inducing functional antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, the mice were immunized by two boosters at 2-week intervals with 25 µg of rPbg37, 25 µg of rPSOP25, mixed proteins (25 µg rPbg37 + 25 µg rPSOP25), or 25 µg rPbg37-PSOP25 chimeric proteins, emulsi ed with incomplete Freund's adjuvant. For antisera, blood was collected 10 days after the third immunization and allowed to clot at room temperature [23,28].…”
Section: Immunization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pfs25 is an important glycophosphatidylinositol-linked protein expressed on the surface of ookinetes. It is found only within the Anopheles host and is approximately 25 kDa with 11 disulfie bonds [118]. The parasites require Pfs25 to survive in the Anopheles's midgut and develop into oocysts [119].…”
Section: Pfs25mentioning
confidence: 99%
“…Other approaches make use of recombinant protein engineering for downstream Pfs25 multimerization [20] or attachment to VLPs [21]. The CoPoP system has been demonstrated for other his-tagged antigens related to malaria transmission-blocking [22,23] and other infectious diseases [24][25][26].…”
Section: Introductionmentioning
confidence: 99%